Technological development and its impact on audience reception: A longitudinal study of IIUM.FM - Mohamed, Shafizan; Wok, Saodah (2017)
In 2011, a study was conducted to look at the audience reception of IIUM.FM, a newly launched online campus radio. Using the Technological Acceptance Model (TAM), the study identified that factors such as perceived ease of use, perceived usefulness, and attitude highly influenced audience reception of the online radio. In 2016, a corresponding study, closely based on the original 2011 study was conducted, to chart and identify how technological changes and developments have further influenced the radio listeners today and whether the factors that determined listenership in 2011 still applies in 2016. The study employs a quantitative research design using the survey method and the questionnaire as the research instrument for data collection. A total of 238 respondents were identified for 2011 and 271 respondents for 2016. The comparisons between the two studies inform about the impact of technological change, its challenges in the radio industry as well as suggesting new trends for audience reception and radio listenership. Their acceptance of the IIUM.FM is similar between 2011 and 2016 cohorts. Same factors influence the actual listening to IIUM.FM. Results of the cohorts do shed some light for recommendation and suggestion to the University’s relevant authorities for further improvement.